1996
DOI: 10.1128/mcb.16.9.4683
|View full text |Cite
|
Sign up to set email alerts
|

Complex Architecture of Major Histocompatibility Complex Class II Promoters: Reiterated Motifs and Conserved Protein-Protein Interactions

Abstract: The S box (also known as at the H, W, or Z box) is the 5-most element of the conserved upstream sequences in promoters of major histocompatibility complex class II genes. It is important for their B-cell-specific and interferon gamma-inducible expression. In this study, we demonstrate that the S box represents a duplication of the downstream X box. First, RFX, which is composed of the RFX5-p36 heterodimer that binds to the X box, also binds to the S box and its 5-flanking sequence. Second, NF-Y, which binds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 47 publications
0
45
2
Order By: Relevance
“…1B) and RFX can bind weakly to this motif in gel retardation assays (48,49). Binding of two RFX molecules to this motif and the X box was found to be cooperative in these studies (48,49). Finally, it was reported that the W box can be converted into a perfect X box sequence without compromising promoter function (49).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1B) and RFX can bind weakly to this motif in gel retardation assays (48,49). Binding of two RFX molecules to this motif and the X box was found to be cooperative in these studies (48,49). Finally, it was reported that the W box can be converted into a perfect X box sequence without compromising promoter function (49).…”
Section: Resultsmentioning
confidence: 98%
“…A widespread model is that the W region could be a duplicated target site for RFX (1,52). This is based on the observation that the W region of the DRA gene contains a sequence that exhibits limited homology to the X box and can be bound weakly by RFX in vitro (44,48,49,53). However, the functional relevance of this finding is not clear because this X box-like motif does not coincide with the most conserved core S sequence.…”
mentioning
confidence: 78%
“…In part, CIITA derives its activity through interaction with the trimeric transcription factor RFX, which is essential for transactivation from the X box and is thought to bind the W box as well (27,40). Voliva et al have shown that the X box of DO␤ can substitute functionally in the DR␣ promoter (54).…”
Section: Rfx Is Essential For Dn␣ and Do␤ Expression In B Cellsmentioning
confidence: 99%
“…RFX is a trimeric protein composed of RFX5 (complementation group C) (22), RFXAP (group D) (23), and RFXANK/RFX-B (group B) (24,25). RFX is thought to direct B cell-specific and IFN-␥-inducible expression of MHC class II genes through binding to the X box (26) and possibly the W box (27). CIITA (group A) (28) is the only MHC class II transcription factor known to be induced in response to IFN-␥, and its expression alone is sufficient to activate expression of the MHC class II genes (29 -31).…”
mentioning
confidence: 99%
“…The general mechanisms of MHC class II expression have been reported (14). Three MHC class II molecules, HLA-DR, -DP, and -DQ, are all regulated by cis-acting promoter elements, W, X1, X2, Y boxes, and their interactions with transcriptional factors such as members of the regulatory factor X family, NF-Y, and CREB have been reported (15)(16)(17). In addition to these binding factors, MHC class II transactivator (CIITA) is also required for efficient promotion of MHC class II genes (18,19).…”
Section: Linical Trials For Cancer Immunotherapy Have Recentlymentioning
confidence: 99%